Childhood Socioeconomic Status and Adult Subjective Wellbeing: The Role of Hope and Sense of Control - Wang, Li; Li, Fenglan; Meng, Keqiang; Dunning, Kelly Heber (Frontiers in Psychology, 2022)
The study investigates the unexplored link between childhood socioeconomic status and adult subjective wellbeing using data from a field survey of 568 rural residents from poor areas in China. This study focuses on exploring the relationship between childhood socioeconomic status, hope, sense of control, and adult subjective wellbeing using a structural equation model. Results indicated that hope and sense of control mediated the links between childhood socioeconomic status and adult subjective wellbeing, revealing that hope and sense of control may buffer the negative impacts of childhood poverty experiences on subjective wellbeing. The findings provide new insights into the impacts of childhood socioeconomic status on adult subjective wellbeing and expand the literature on key factors in adult subjective wellbeing.